CCAFS 3rd Independent Science Panel Meeting, Ouagadougou, Burkina Faso, 24-25 October 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
In October 2012 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its third Independent Science Panel meeting in Burkina Faso.